Exploring teachers’ perceptions in managing interracial interactions in a multicultural setting: a case study of five Malaysian secondary schools in Klang Valley - Othman, Azam; Sheikh Ahmad, Ismail; Abdul Rahman, Hamidon; Shabu, Shahrul Fhaizal (IIUM PRESS, 2013)
The multicultural school environment at the Malaysian national schools presents a number of issues and challenges for the in-service teachers. This study investigated the experiences of 16 teachers in five selected national type schools in Klang Valley. Through a series of semi-structured interviews, responses from the teachers provided insights to the multiculturalism school environment in a multiracial society such as Malaysia. The findings of this study revealed that low proficiency of the national language among non-Malay students, inadequate multicultural trainings for teachers, and lack of programmes and initiatives that promote unity in a multicultural environment are among the major hurdles faced by teachers. The implications of the findings and recommendations from the teachers on ways to improve the multicultural environment in schools are also presented.